L’approche sociologique de l’Anthropocène : un nouveau cadre historique des rapports sociaux - Eric Macé (Les Cahiers de Framespa)
The unprecedented scale of contemporary environmental upheavals has been referred to as the "Anthropocene" era by Earth system specialists. This article shows that this new environmental reality has collided with the main epistemological and cognitive framework of the social sciences, which was modernity, which did not imagine a social world so interdependent with non-humans and so vulnerable as to risk disappearing. After a first part that describes these shifts, the second part shows that this "anthropocene moment" also reconfigures social power relations, leading to a sociology of new conflictualities related to "transition" issues.